International Wheat Agreements and Problems, 1949-56 - Farnsworth, Helen C. (Quarterly Journal of Economics, 1956)
Introduction, 217. — I. Terms and objectives of the current Agreement, 217. — II. The IWA in the world wheat economy, 220. — III. Basic objectives unfulfilled, 232. — IV. The world's real wheat problems and more appropriate objectives, 241.